Participação do canal TRPV4 na nocicepção e neuroinflamação induzida em um modelo de síndrome de dor regional complexa do tipo 1 em camundongos - Silva, Náthaly Andrighetto Ruviaro da (2024)
Complex Regional Pain Syndrome Type I (CRPS-I) is a debilitating pain condition that can occur following surgery, fractures, or limb trauma, which may lead to ischemia/reperfusion. However, the acute and chronic pain associated with this disease remains challenging to manage. The transient receptor potential vanilloid 4 (TRPV4) receptor is involved in the mechanisms underlying neuropathic and inflammatory pain. Therefore, it could be a promising new pharmacological target for treating CRPS-I. Thus, this study aimed to evaluate the involvement of the TRPV4 channel in nociception induced by a CRPS-I model in mice. Male mice (C57BL/6, 20-30g) were used to induce chronic post-ischemia pain (CPIP), an animal model of CRPS-I. Mechanical allodynia, thermal hyperalgesia, body weight, and the rotarod test were conducted before (baseline) and post-CPIP induction (days 1, 5, 10, and 15). The open field test was performed on days 1 and 15 post-CPIP induction, and nest-building behavior was assessed overnight on the 15th to the 16th day post-induction. On the 16th day, the animals were euthanized, and sciatic nerve, spinal cord, and plasma samples were collected for analysis of hydrogen peroxide (H2O2) and nitric oxide (NO) levels. Additionally, spinal cord samples were used for gene expression analysis of Par2, Trpv4, Gfap, and Nfr2 by PCR. Additionally, the antinociceptive and neuroprotector effect of repeated treatment (for 15 days) with the selective TRPV4 receptor antagonist (HC-067047, 1 mg/kg, intraperitoneal) was evaluated. It was found that from day 1 to day 15 after CPIP induction, the animals developed mechanical allodynia and thermal hyperalgesia, without changing locomotor or weight parameters. Repeated treatment with HC-067047 showed antinociceptive effects from day 5 to day 15 after CPIP induction. CPIP-Veh (vehicle) animals exhibited reduced time spent in the central zone in the open field test, and treatment with the TRPV4 antagonist reversed this parameter. Moreover, CPIP animals showed reduced nest-building scores on day 16, whereas mice receiving repeated treatment with HC-067047 displayed typical nest-building behavior. Furthermore, increased levels of TRPV4 agonists, H2O2 and NO, observed in CPIP-Veh, were reduced following 15 days of repeated HC-067047 treatment. CPIP induction also caused an increase in the gene expression of Par2, Trpv4, Gfap, and Nfr2. After HC-067047 treatment, the expression of these markers was reduced, except for Trpv4, which remained elevated. Thus, the TRPV4 channel is likely involved in the nociceptive mechanism of the CPIP model in mice and may represent a novel treatment strategy.